Tailoring the interfacial strength of basalt fibres/epoxy composite with ZnO-nanorods. Issue 8 (3rd August 2021) - Lilli, Matteo; Sbardella, Francesca; Bavasso, Irene; Bracciale, Maria Paola; Scheffler, Christina; Rivilla, Ivan; Tirillo', Jacopo; Xin, Wenbo; De Rosa, Igor Maria; Sarasini, Fabrizio
ABSTRACT: The presence of a secondary phase between the fibres and the matrix has proved to be a good approach for interphase tailoring for enhanced load transfer. In this regard, an optimization of the low-temperature hydrothermal growth process of ZnO-nanorods on different basalt substrates as a function of different growth times was performed. Scanning electron microscope and X-ray diffraction analysis revealed the best results in terms of homogeneity and uniformity of the ZnO nanostructures for the longest growth time, i.e., 5 h for basalt fabrics and 120 minutes for single basalt fibres. The presence of ZnO nanostructures induced a hydrophobic behaviour with contact angles up to 116° for 4- and 5-h growth processes. Fibre/matrix adhesion was characterized by single fibre pull-out tests, showing a 16% increase in interfacial strength. ZnOs added also photocatalytic properties to basalt fibres, enabling a selective removal of organic pollutant equal to 37%.